HOW TO BUILD AND MAINTAIN EMOTIONAL CONNECTION WITH COSTUMER TO INCREASE BRAND AWARENESS A STUDY CASE OF COOKIEGOM - Nindya Kalisha Putri; Ilma Aulia Zaim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Indonesian soft cookie market is highly competitive, making emotional connection a key driver of customer loyalty. This study examines how customers form emotional connections with cookie brands and how Cookiegom, a small business, can strengthen these connections to enhance brand awareness and repeat purchase. A qualitative approach was applied through in-depth interviews with ten consumers who had purchased both Cookiegom and Doughlab, supported by digital observation of social media and customer reviews. Thematic analysis reveals that Cookiegom is perceived as a “comfort brand,” offering warmth, comfort, and freshness, while Doughlab is viewed as a premium, highly visible brand. These emotional differences influence attachment, repeat purchases, and word-of-mouth behavior. The study proposes the Emotional Comfort Connection Loop Model to explain how emotional bonds develop through repeated experiential cycles. Strengthening emotional storytelling, improving digital consistency, and integrating comfort-oriented touchpoints are recommended strategies for Cookiegom.